Surface binding, localization and storage of iron in the giant kelp Macrocystis pyrifera. Issue 4 (24th March 2016) - Miller, Eric P.; Auerbach, Hendrik; Schünemann, Volker; Tymon, Teresa; Carrano, Carl J.
Abstract : Iron binding to the cell surface of marine macroalgae, such as the giant kelp Macrocystis pyrifera, through alginate carboxylate groups may have biological significance as an iron storage mechanism. Abstract : Iron is an essential element for all living organisms due to its ubiquitous role in redox and other enzymes, especially in the context of respiration and photosynthesis. Although the iron uptake and storage mechanisms of terrestrial/higher plants have been well-studied, the corresponding systems in marine algae have received far less attention. While the iron many marine algae take up from the environment, irrespective of its detailed internalization mechanism, arrives at the cell surface by diffusion, there is growing evidence for more "active" means of concentrating this element prior to uptake. It has been well established in both laboratory and environmentally derived samples, that a large amount of iron can be "non-specifically" adsorbed to the surface of marine algae. While this phenomenon is widely recognized and has prompted the development of experimental protocols to eliminate its contribution to iron uptake studies, its potential biological significance as a concentrated iron storage source for marine algae is only now being recognized. In this study, using an interdisciplinary array of techniques, we show that the giant kelp Macrocystis pyrifera also displays significant cell surface bound iron although less than that seen with the related brown alga Ectocarpus siliculosus. The iron on the surface is likely bound to carboxylate groups and once inside the iron is found to localize differently depending on cell type. Iron appears to be stored in an as yet undefined mineral phase.